MODEL PEMBELAJARAN KOOPERATIF (COOPERATIVE LEARNING) - Henny Sukmawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Cooperative Learning is a learning system which is known as group learning process, Cooperative learning prioritizes a group working in solving a problem to apply the knowledge and skill to get the goal of learning process. It is also hoped that it can improve the result of students’ cognitive ability. Cooperative learning can improve students’ academic achievement, either talented students or low capalibity students. The most important thing is students appreciate each other, they build their friendship through this learning model. Cooperative learning is a group learning that can be continued by educators to apply in learning process.